Pengaruh Ukuran Prusahaan, Profitabilitas, Leverage Dan Kepemilikan Institusional Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2014) - Pramudhita, Yusuf Adhi; , Drs. Eko Sugiyanto, M.Si (2017)
Earnings management is an action manager to choose accounting policies or actions that affect their earnings, so in order to achieve certain goals in reporting earnings. This study aims to determine the effect of firm size, profitability, leverage and institutional ownership on earnings management in manufacturing companies listed in Indonesia Stock Exchange 2012-2014. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange 2012-2014. This study using purposive sampling with predetermined criteria. The samples used 150 companies. The analysis technique used is multiple linear regression analysis. The results showed that the only variable firm size and profitability effect on earnings management. While variable leverage and institutional ownership has no effect on earnings management..